2016
DOI: 10.1002/ajmg.b.32467
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the endocannabinoid system and response to Cognitive Behavior Therapy for child anxiety disorders

Abstract: Extinction learning is an important mechanism in the successful psychological treatment of anxiety. Individual differences in response and relapse following Cognitive Behavior Therapy may in part be explained by variability in the ease with which fears are extinguished or the vulnerability of these fears to re‐emerge. Given the role of the endocannabinoid system in fear extinction, this study investigates whether genetic variation in the endocannabinoid system explains individual differences in response to CBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 65 publications
0
23
1
Order By: Relevance
“…Moreover, a favorable and a poorer response during the active treatment period were associated with minor allele of rs12133557 and rs6454676, respectively. Regarding the CNR2 gene, unlike to previous findings in depression [81], the rs2501431 genotype was not associated with anxiety symptoms or treatment response [99].…”
Section: Cannabinoid Receptors In Anxietycontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, a favorable and a poorer response during the active treatment period were associated with minor allele of rs12133557 and rs6454676, respectively. Regarding the CNR2 gene, unlike to previous findings in depression [81], the rs2501431 genotype was not associated with anxiety symptoms or treatment response [99].…”
Section: Cannabinoid Receptors In Anxietycontrasting
confidence: 99%
“…This makes the endocannabinoid signaling quite sensitive for developmental fluctuations due to environmental causes, which may increase the risk of anxiety and other stress-related disorders. Interestingly, a recent study show the impact of the variation in the CNR1, CNR2, and FAAH genes in a sample of children with a primary anxiety disorder diagnosis [99]. These authors nicely reported an association between two SNPs (rs12133557 and rs6454676) in the CNR1 gene and the change in symptom severity in both the entire sample and a subset of patients with fear based diagnoses [99].…”
Section: Cannabinoid Receptors In Anxietymentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, Kathryn Lester, Thalia Eley and colleagues have pursued a genetic approach to predicting response to psychosocial therapies (dubbed “therapygenetics”) analogous to traditional pharmacogenetic research. In this issue, they report a genetic analysis of CBT for childhood anxiety disorders in the largest such analysis to date (comprising more than 1,300 children) [Lester et al, ]. The analyses focused on genes in the endocannabinoid system which has been shown to mediate fear extinction, a key mechanism in CBT for pathologic anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kathryn Lester, Thalia Eley and colleagues have pursued a genetic approach to predicting response to psychosocial therapies (dubbed "therapygenetics") analogous to traditional pharmacogenetic research. In this issue, they report a genetic analysis of CBT for childhood anxiety disorders in the largest such analysis to date (comprising more than 1,300 children) [Lester et al, 2016]. The analyses focused on genes in the endocannabinoid system which has been shown to mediate fear extinction, a key mechanism in CBT for pathologic anxiety.…”
Section: Introductionmentioning
confidence: 99%